Effect of liraglutide on the Janus kinase/signal transducer and transcription activator (JAK/STAT) pathway in diabetic kidney disease in db/db mice and in cultured endothelial cells. Issue 8 (28th February 2019) - Zitman‐Gal, Tali; Einbinder, Yael; Ohana, Meital; Katzav, Aviva; Kartawy, Amany; Benchetrit, Sydney
Abstract: Background: Emerging evidence demonstrates the involvement of Janus tyrosine kinase/signal transducer and transcription activator (JAK/STAT) proteins in the pathophysiology of diabetic kidney disease (DKD). The JAK/STAT pathway is involved in the inflammatory response and endothelial cell dysfunction observed in DKD. The glucagon‐like peptide‐1 (GLP‐1) analog liraglutide is an effective treatment for type 2 diabetes because it improves the inflammatory changes observed in experimental models of DKD. This study used db / db mice and endothelial cells (ECs) to determine the effect of diabetic environment on the JAK/STAT pathway and to assess the potential effect of liraglutide (200 μg/kg) in both models. Methods: Diabetic db / db mice (12 weeks old) were treated with liraglutide for 14 weeks. The kidneys were then perfused with saline and removed for mRNA, protein, and immunohistochemical analyses. Endothelial cells were stimulated advanced glycation end products (AGEs) (200 μg/μL) glucose (200 mg/dL) and liraglutide (100 nM) for 24 hours. Total RNA and protein were extracted and analyzed for expression of JAK/STAT signaling. Results: Phosphorylated (p‐) STAT3 was significantly upregulated in db / db mice compared with non‐diabetic mice. Liraglutide significantly downregulated p‐STAT3 protein expression in db / db mice. In db / db mice, p‐STAT3 was primarily expressed in the glomeruli, whereas p‐JAK2 was also expressed in kidney tubules. In ECs, liraglutide treatment prevented increased expression of p‐STAT3 and p‐JAK2. Liraglutide inhibited the target gene suppressor of cytokine signaling 3 ( SOCS3 ) and sirtuin 1 ( SIRT1 ) in db / db mice and in cultured EC. Conclusions: This study suggests that the GLP‐1 analog liraglutide inhibits the JAK/STAT pathway, which participates in intracellular processes in experimental models of diabetes. Abstract : Highlights Diabetic conditions elevated expression of signal transducer and activator of transcription (STAT) 3 and Janus tyrosine kinase (JAK) 2. Diabetic conditions elevated expression of suppressor of cytokine signaling 3 and sirtuin 1 (SIRT1). The glucagon‐like peptide‐1 (GLP‐1) analog, liraglutide, is an inhibited STAT3/JAK2 expression, possibly through SIRT1 signaling. 摘要: 背景: 越来越多的证据表明Janus酪氨酸激酶/信号转导与转录激活因子(Janus tyrosine kinase/signal transducer and transcription activator，JAK/STAT)蛋白参与了糖尿病肾病(diabetic kidney disease，DKD)的病理生理学过程。在DKD中观察到的炎症反应以及内皮细胞功能障碍与JAK/STAT通路有关。胰高血糖素样肽‐1(glucagon‐like peptide‐1，GLP‐1)类似物利拉鲁肽是一种有效的2型糖尿病治疗药物，因为在DKD实验模型中观察到它可以改善炎症反应。这项研究利用db/db小鼠与内皮细胞(endothelial cells，ECs)来测定糖尿病环境对JAK/STAT通路的影响，并且在这两个模型中评估了利拉鲁肽(200 μg/kg)的潜在影响。 方法: 糖尿病db/db小鼠(12周龄)使用利拉鲁肽治疗14周。然后在肾脏中灌入生理盐水，取出后进行mRNA、蛋白质以及免疫组化分析。使用晚期糖基化终产物(200 μg/μL)、葡萄糖(200 mg/dl)与利拉鲁肽(100 nM)刺激内皮细胞24小时。提取出全部的RNA与蛋白质并且分析了JAK/STAT信号的表达。 结果: 与非糖尿病小鼠相比较，在db/db小鼠中磷酸化STAT(p‐ STAT3)显著上调了。在db/db小鼠中利拉鲁肽可以显著下调p‐STAT3蛋白的表达。在db/db小鼠中，p‐STAT3主要在肾小球中表达，而p‐JAK2在肾小管中也有表达。在ECs中，使用利拉鲁肽治疗后可以防止p‐STAT3与p‐JAK2表达增加。在db/db小鼠以及培养的EC中，利拉鲁肽可以抑制细胞因子信号3(suppressor of cytokine signaling， SOCS3 )以及sirtuin 1( SIRT1 )的靶基因抑制因子。 结论: 这项研究表明，GLP‐1类似物利拉鲁肽可以抑制JAK/STAT通路，这个通路与糖尿病实验模型的细胞内进程有关。